Comprehensive chemical secretory measurement of single cells trapped in a micro-droplet array with mass spectrometry. Issue 22 (6th February 2015) - Fujita, Hideaki; Esaki, Tsuyoshi; Masujima, Tsutomu; Hotta, Akitsu; Kim, Soo Hyeon; Noji, Hiroyuki; Watanabe, Tomonobu M.
Abstract : By trapping individual single cells in a micro-well, molecules secreted by a single cell can be analyzed using mass spectrometry. Abstract : Secretomics, the comprehensive study of cell releasates, offers a non-invasive approach to understanding cell heterogeneity. We here propose single cell small molecule secretomics using micro-droplet arrays and mass spectrometry as a new repertoire of omics technologies. The present method revealed the heterogeneity of secreted small molecules from individual single cells without the use of any invasive processes.